Design and synthesis of an amino-functionalized non-fullerene acceptor as a cathode interfacial layer for polymer solar cells. Issue 15 (25th March 2020) - Luo, Peng; An, Kang; Ying, Lei; Li, Guanze; Zhu, Chunguang; Fan, Baobing; Huang, Fei; Cao, Yong
Abstract : A non-fullerene acceptor with amino groups can be used as a cathode interlayer to enhance the photovoltaic performance. Abstract : A novel n-type organic small-molecule semiconductor, denoted N-IDTBR, was designed and synthesized by introducing an amine group into the extensively used non-fullerene acceptor O-IDTBR . This new material can be readily dissolved in alcohol, which allowed it to be spin-cast on top of a photoactive layer by processing with an orthogonal solvent for the construction of multilayer polymer solar cells. A poly(3-hexylthiophene):O-IDTBR blend was selected as a model system, which contains N-IDTBR as the cathode interlayer. We adopted non-halogenated anisole/2-methylanisole as the processing solvent to fabricate the active layer and achieve an impressive power conversion efficiency of 6.1%. Of particular interest is the fact that the N-IDTBR functioned not only as a single cathode interfacial layer to facilitate charge collection, but it also presented slight contribution to the light-harvesting capability of the device, thus leading to enhanced current density of the resulting devices. More importantly, the PCEs of the devices remained at 5.85 ± 0.25% as the thickness of the N-IDTBR layer varied from 5 to 30 nm, which demonstrated their great potential for future practical applications.